Speech Act dalam Headline Berita Media Online - Riris Tiani (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The development of pragmatic strategy in the journalistic process has an effect on the image of the person who has been reported. Directly or not, imaging of political figures to public figures is influenced by pragmatic strategies packed with journalists in the news media. Political figures until the public figure collaborate to create an interesting impression. An interesting impression or positive image will change the concept of society over this overnight assessment. The higher the pragmatic power journalists developed in writing the news, the better the quality of the news will be. In accordance with the results of pragmatic strategy research on Headline news on Republika.co.id can be concluded that in the creation of news headlines have implemented pragmatic strategy. The dominant pragmatic strategy used is the illocution act. The illusionary strategy becomes dominant because the news content that is headlined is dominated by political and economic news. So the development of explaination techniques more highlighted.